Exchange rate forecasts and expected fundamentals - Christian D. Dick; Ronald MacDonald; Lukas Menkhoff (Kiel Institute for the World Economy (IfW), 2014)
Using a large panel of individual professionals' forecasts, this paper demonstrates that good exchange rate forecasts are related to a proper understanding of fundamentals, specifically good interest rate forecasts. This relationship is robust to individual fixed effects and further controls. Reassuringly, the relationship is stronger during phases when the impact from fundamentals is more obvious, e.g., when exchange rates substantially deviate from their PPP values. Finally, forecasters largely agree that an interest rate increase relates to a currency appreciation, but only good forecasters get expected interest rates right.
Keywords: F31; F37; E44; 330; Exchange Rate Determination; Individual Expectations; Macroeconomic Fundamentals